2017
DOI: 10.1186/s12864-017-4155-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization, evolution, and expression analysis of the leucine-rich repeat receptor-like protein kinase (LRR-RLK) gene family in Rosaceae genomes

Abstract: BackgroundLeucine-rich repeat receptor-like protein kinase (LRR-RLK) is the largest gene family of receptor-like protein kinases (RLKs) and actively participates in regulating the growth, development, signal transduction, immunity, and stress responses of plants. However, the patterns of LRR-RLK gene family evolution in the five main Rosaceae species for which genome sequences are available have not yet been reported. In this study, we performed a comprehensive analysis of LRR-RLK genes for five Rosaceae speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 75 publications
5
56
0
Order By: Relevance
“…Furthermore, we have also taken note that the coherent miRNA targets included (a) several TFs that were predicted to be targeted by miRNA regulators, for example, sca‐miR164d targets FAR1, sca‐miR530 targets MYB, sca‐miR396a targets Trihelix, and sca‐miR5139a targets VOZ1‐like, suggesting that these miRNAs may operate to enhance the adaptation of hexaploid cytotypes through an integrative miRNA‐TF‐mRNA regulatory network; (b) receptor‐like protein kinases (RLKs) that were predicted to be targets of multiple miRNAs such as sca‐miR161a, sca‐miR5139a, sca‐miR5139b, and sca‐miR8155. This target is an important enzyme gene and functions in regulating plant growth, development, signal transduction, immunity, and stress responses (Sun, Li, Wang, Zhang, & Wu, ). Notably, these RLK genes were remarkably up‐regulated in hexaploid cytotypes, suggesting that their regulator miRNAs may play key roles in the environmental adaptation of hexaploid cytotypes; (c) unigenes associated with methylation and ubiquitination processes, such as histone‐lysine N ‐methyltransferase (CL7649.Contig3_All), ubiquitin‐protein ligase (CL2235.Contig13_All), U‐box domain‐containing protein (CL2207.Contig4_All), and F‐box protein (Unigene1223_All), that were predicted to be targets of sca‐miR396d, sca‐miR444a, sca‐miR393d, and sca‐miR5139a, suggesting that these unigenes may be subjected to miRNA‐mediated DNA methylation and ubiquitination; and (d) two dirigent protein genes (CL6884.Contig1_All and CL6884.Contig3_All) that were predicted to be targets of sca‐miR169d.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have also taken note that the coherent miRNA targets included (a) several TFs that were predicted to be targeted by miRNA regulators, for example, sca‐miR164d targets FAR1, sca‐miR530 targets MYB, sca‐miR396a targets Trihelix, and sca‐miR5139a targets VOZ1‐like, suggesting that these miRNAs may operate to enhance the adaptation of hexaploid cytotypes through an integrative miRNA‐TF‐mRNA regulatory network; (b) receptor‐like protein kinases (RLKs) that were predicted to be targets of multiple miRNAs such as sca‐miR161a, sca‐miR5139a, sca‐miR5139b, and sca‐miR8155. This target is an important enzyme gene and functions in regulating plant growth, development, signal transduction, immunity, and stress responses (Sun, Li, Wang, Zhang, & Wu, ). Notably, these RLK genes were remarkably up‐regulated in hexaploid cytotypes, suggesting that their regulator miRNAs may play key roles in the environmental adaptation of hexaploid cytotypes; (c) unigenes associated with methylation and ubiquitination processes, such as histone‐lysine N ‐methyltransferase (CL7649.Contig3_All), ubiquitin‐protein ligase (CL2235.Contig13_All), U‐box domain‐containing protein (CL2207.Contig4_All), and F‐box protein (Unigene1223_All), that were predicted to be targets of sca‐miR396d, sca‐miR444a, sca‐miR393d, and sca‐miR5139a, suggesting that these unigenes may be subjected to miRNA‐mediated DNA methylation and ubiquitination; and (d) two dirigent protein genes (CL6884.Contig1_All and CL6884.Contig3_All) that were predicted to be targets of sca‐miR169d.…”
Section: Resultsmentioning
confidence: 99%
“…Upon ligand binding, these LRR‐RKs recruit another LRR‐RK, BAK1, for transducing the signal to the cytosol . Although it has been often reported that LRR‐RKs interact with each other through their extracellular domains (ECDs) , a comprehensive analysis on LRR‐RK interactions is confounded by a massive expansion of this class of receptor proteins in plants . By employing a high‐throughput in vitro interaction assay, Smakowska‐Luzan et al .…”
Section: Immune Receptor Networkmentioning
confidence: 99%
“…PKs play important roles in signaling networks including the perception of biotic agents, light quality and quantity, phytohormones, and various environmental conditions [42]. Fiftyseven (29 up-regulated and 28 down-regulated), sixty-two (43 up-regulated and 19 down-regulated), and fifty (43 up-regulated and 17 down-regulated) PKs were identified among the meta genes at LG, TR, and PR phases, respectively (S3 Table).…”
Section: Identification Of the Transcription Factors (Tfs) Transcripmentioning
confidence: 99%